Invasive thymoma with intravascular growth into the great veins and right atrium: A case report - Wang Shen; Yang Cao; Xinyun Wang; Peng Zhang; Qinghua Zhou (Thoracic Cancer, 2020)
Here, we present a case of invasive thymoma with intraluminal growth into the left and right brachiocephalic veins, superior vena cava and the right atrium. Resection of the mass, double partial upper lobe lobectomy and superior vena cava, and left and right brachiocephalic vein replacement were performed. Pathological diagnosis indicated a mixed histological pattern indicative of type B1 and type B2 thymoma, predominantly type B2 thymoma. The patient was well and without local recurrence or distal metastasis after 50 months of follow‐up.